Understanding Shifting Power Relations within and across Organizations: A Critical Genre Analysis - Levina, Natalia; Orlikowski, Wanda J. (Academy of Management Journal, 2009)
Drawing on an in-depth qualitative study of a consulting project, we examine how conditions of novelty and ambiguity on interorganizational engagements produce inconsistent norms and expectations for guiding project interaction. Clients and consultants attempt to resolve the resulting discursive tensions while also increasing their organization's influence on the project. As diverse institutional contexts offer multiple legitimate ways of practicing, agents draw on such alternatives to renegotiate power relations. We develop a theoretical framework and empirical approach for understanding how discursive resources from diverse institutional contexts can be used to transform power relations within and between organizations.